Assessing the accuracy and reliability of freeway traffic monitoring stations using GPS probe vehicle speed data. (2nd August 2011) - Chaudhuri, Piyali; Stevanovic, Aleksandar; Martin, Peter
Freeway performance measures are extracted from Traffic Monitoring Stations (TMS) which gather traffic volume and speed data. Reported freeway speeds are usually aggregated over periods of 20 or 30-second or 1, 5, or 15-minute by traffic agencies. This paper examines the accuracy and reliability of reported TMS detector speeds. The study compares speeds collected by GPS-equipped probe vehicles with aggregated detector speeds. The paper evaluates how various aggregation intervals impact accuracy and reliability of TMS detector speeds and determines the optimal aggregation interval. Results indicate that shorter aggregation intervals are appropriate for high variability traffic conditions during peak periods.